Advances in Nuclear Physics, Volume 26 - Negele, J.W; Vogt, Erich W (Springer, 2001)
This volume contains three review articles pertaining to three different problems of great interest for nuclear physics. One article deals with the origin of spin in the quark model for neutrons and protons, as measured with beams of electrons and muons. Another deals with the evidence for liquid-to-gas phase transitions in relativistic collisions of nuclei. The third deals with the very unusual bands of energy levels of very high spin which are found when nuclei achieve a very high rotation.